The Values Of Democracy In The Implementation Local Political Agenda In Kendari - Jamal Bake (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The objective  research are: 1) Describe and analyze the application of the values of democracy that is a participate guarantee, stakeholders representation, equal rights in the decision making, dissemination of information, responsiveness, and supervision community, implemented in stage of local political agenda at Kendari 2) Describe and analyze the community consistency to participate in the implementation of local political agenda at Kendari. (12) Using qualitative research, done interviews with informan, focused group discussion (FGD), observation and documents study.The result of research are: 1) The values of democracy as described Dahl namely: citizens guarantee to participate, stakeholders representation, equal rights of the community in decision-making, transparency, community control, responsiveness and accountable, manifested in every stage the implementation of the election mayor in Kendari. Implementation of  local politic agenda that accompanied by the rule can prevent the conflict and able to create a harmonious and safe democracy. 2) The general, local communities are consistent to participate in the election mayor, it can be seen from a commitment and our deepest concern residents to create the high-quality election, and political rights motivation to use that constituted by awareness to give birth to local leaders. However, it is still there are communities who have not yet been consistent participate in local political agenda.Need to enlightenment on, so that the people are aware that mayor election means provide the values of democracy, using the right politics is an ideal, and carrying out a quality local political agenda.